Shaping sustainable perceptions: The role of metaphors in Olympic news discourse - Wei Peng (PLoS ONE, 2025)
The dissemination of sustainable development concepts in large international events like the Olympics has garnered great attention. As a major international sports event, the Beijing Winter Olympics served as an important platform for showcasing China’s sustainable development philosophy through its official news coverage. In this context, metaphor, as a powerful cognitive tool, plays a crucial role in shaping public perception and facilitating the dissemination of values by mapping concrete source domains onto abstract target domains. This paper constructs a critical metaphor analysis framework for sustainable development, analyzing the mechanisms by which metaphors map the concepts of social, economic, and ecological sustainability, and their multifaceted roles in conveying policy proposals, ideologies, cultural values, and social group behaviors. The findings indicate that metaphors effectively facilitate public understanding of sustainability by concretizing abstract concepts. In the social dimension, metaphors emphasize fairness, cultural diversity, and social solidarity; in the economic dimension, they highlight resource recycling, technological innovation, and industrial upgrading; while in the ecological dimension, the focus is on environmental protection and the harmonious coexistence of humanity and nature. Metaphors play a crucial role in shaping public perceptions of policy, reflecting specific values and socio-cultural contexts, facilitating cultural communication and understanding, and enhancing public responsibility and participation awareness.